Removal of Some Heavy Metals from Polluted Water Using New Schiff Base for Polyacrylamide with Zeolite Nanocomposites - Zainab Sabeer Abdulsada; Sahar S. Hassan; Sanaa Hitur Awad (مجلة بغداد للعلوم, 2024)
This work involved the preparation of a new Schiff base ligand derived from poly acrylamide and glutaraldehyde [(2S, 2'S) – N, N' - (pentane-1, 5-diylidene) bis (2- methylbutan amide)] (PAAG) with some heavy metals (Cr +3, Mn + 3, Fe + 3, Co + 2, Ni + 2, Cu + 2, Zn + 2, Cd + 2) to produce corresponding complexes. Schiff bases and their metal complexes are characterized using FTIR spectral, Uv-Vis spectroscopy, conductivity, magnetic moments, Thermal gravimetric analysis (TGA), x-ray diffraction, scanning electron microscope (SEM) and atomic force microscope (AFM). The prepared polymer was used with zeolite to form composite material to remove some of the elements from polluted water that were drawn from industrial water of the electric power plants in Dora and South Baghdad. Also, estimate the elements trace concentrations before and after using the prepared base by atomic absorption spectroscopy.